Capability and diversity of Cellulolytic bacteria isolated from three tropical habitats in Boyaca, Colombia - Paola Andrea Viteri Florez; David Arturo Castillo Guerra; Silvio Edgar Viteri Rosero (Acta Agronómica)
In the majority of developing countries the research on the cellulolytic microorganisms has been scarcely oriented to the transformation of organic solid waste into compost, ignoring their enormous industrial potential. The main objective of the present investigation was to generate information on the capacity and diversity of the cellulolytic bacteria isolated from three different habitats. The study included soil samples from native forests and cereal producing farms as well as from compost piles. From each sample, a serial dilution until 10-4 was prepared and from each dilution test tubes containing liquid mineral medium and a strip of filter paper as a source of cellulose were inoculated. After three weeks of incubation, the population density of the cellulolytic microorganisms was estimated and from the filter paper strips streaks were made on nutrient agar medium and then on solid mineral medium, supplemented with cellulose. The bacterial growths were submitted to the Congo Red test and the ones with the greater potential were identified. In comparison to the soils the compost piles harbor a higher population density of cellulolytic microorganisms. In respect to the cellulolytic bacteria, in total were obtained 20 isolates, 19 from the native forests and 1 from a compost pile. Isolates 1, 2, 6, 7 and 14 showed a higher cellulolytic capacity with halos of hydrolysis between 0.65 and 0.30 cm. Isolate 1 was identified as Bacillus sp, isolate 7 as Pseudomonas sp, and isolate 6 as Erwinia sp. This information is useful to explore with confidence the potential of the cellulolytic bacteria in the industry.